The Effect of Impulsive Buying in Paylater Usage on Psychological Well-Being in Students - ayu, selly candra (Proceedings Conference Psychology and Flourishing Humanity; Vol 2 No 1 (2025): Proceedings Conference on Psychology and Flourishing Humanity, 2026)
The development of financial technology, particularly the paylater feature, makes it easier for students to make transactions, but also has the potential to increase impulsive buying behavior. This study aims to examine the effect of impulsive buying on the psychological well-being of students who use Paylater. A quantitative method was used with a causal-comparative design. The research sample consisted of 342 students aged 18–25 who used Paylater services, selected through purposive sampling. The research instruments included the Impulse Buying Tendency Scale (Verplanken & Herabadi, 2001) and the Psychological Well-Being Scale (Ryff, 1989). Data analysis used Pearson's correlation and simple linear regression. The results showed a strong and significant negative relationship between impulsive buying and psychological well-being (r = –0.907, p < 0.001). Regression analysis showed R² = 0.822, which means that 82.2% of the variation in psychological well-being is explained by impulsive buying. The higher the level of impulsive buying, the lower the psychological well-being of students. These findings emphasize the importance of financial literacy and self-control in the use of paylater services